Repurposing ibuprofen-loaded microemulsion for the management of Alzheimer's disease: evidence of potential intranasal brain targeting - Ming Ming Wen; Noha Ismail Khamis Ismail; Maha M. A. Nasra; Amal Hassan El-Kamel (Taylor & Francis Group, 2021)
Studies have shown the use of non-steroidal anti-inflammatory drugs, such as ibuprofen could reduce the risk of Alzheimer's disease. The drug-repurposing strategy offers a bright opportunity for these patients. Intranasal administration through the olfactory pathway provides noninvasive and direct drug delivery to the target brain. A novel ibuprofen microemulsion was prepared, characterized and assessed the brain uptake in rats. The solubility of ibuprofen in various oils, surfactants, co-surfactants, and different ratios of surfactant/co-surfactant mixtures was screened and the phase diagrams were constructed. The colloidal particle size was 166.3 ± 2.55 nm and the zeta potential was −22.7 mV. Conductivity and dilution test identified an O/W type microemulsion with pH 4.09 ± 0.08. The rheological study showed a Newtonian flow behavior with cP 10.633 ± 0.603 (mPa⋅s). A steady drug release and linear permeation profiles were observed and showed a 90% permeation rate from the released drug. Ibuprofen microemulsion showed excellent stability in 3-months accelerated storage conditions, heating-cooling and freeze-thaw cycles, accelerated centrifugation, and 6- and 12-months long-term storage conditions. In vivo studies in rats further demonstrated a 4-fold higher brain uptake of ibuprofen from the microemulsion compared to the reference solution and nearly 4-fold and 10-fold higher compared to the intravenous and oral administrations. This study provides an exciting repurposing strategy and new administration route for the treatment of Alzheimer's disease.